ECOLOGICAL SERVICES OF AGROFORESTRY LANDSCAPES IN SELECTED WATERSHED AREAS IN THE PHILIPPINES AND INDONESIA - Romnick S. Baliton; Christine Wulandari; Leila D. Landicho; Rowena E. D. Cabahug; Roselyn F. Paelmo; Reynaldo A. Comia; Roberto G. Visco; Pitojo Budiono; Susni Herwanti; Rusita Rusita; Arnold Karl SA. Castillo (BIOTROPIA, 2017)
This article argues that the practice of agroforestry provides ecological contributions to smallholder farmers cultivating in watershed areas. Specifically, this farming system contributes to the carbon sequestration potential of woody perennials and the biodiversity conservation of other system components. This argument is based on research conducted in the Molawin-Dampalit Sub-Watershed, Mt. Makiling Forest Reserve in the Philippines, and the Way Betung Watershed in Indonesia. The research involved interview sessions with 106 and 261 smallholder farmers, and the assessment of 27 and 14 agroforestry plots for carbon stock assessment and biodiversity assessment, respectively. Results indicated that the total carbon found among the crop components was 52.32 MgC/ha in the Molawin-Dampalit Sub-Watershed and 244.26 MgC/ha in the Way Betung Watershed, suggesting a high carbon sequestration potential of woody perennials and understory crops in an agroforestry system. The farm lots cultivated by smallholder farmers were found to contribute to biodiversity conservation, having a moderate biodiversity index of 2.59 and 2.53, respectively. With these findings, the promotion of desired agroforestry systems in suitable portions of watershed areas should be intensified to contribute to ecological balance across the landscape. Agroforestry should always be an integral part of all initiatives toward ecological restoration, with cultivators or smallholder farmers as potential partners. The agroforestry system should consider all technical and socioeconomic factors to ensure diverse components and provide food security for smallholder farmers throughout the year.